2004
DOI: 10.1373/clinchem.2004.035832
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Ten Second-Generation (Human) Tissue Transglutaminase Antibody Assays in Celiac Disease

Abstract: Background: Anti-tissue transglutaminase (tTG) assays that use human tTG as antigen have recently become available. We evaluated commercially available assays with human tTG antigen to estimate their diagnostic accuracies and to determine whether they agree sufficiently to be used interchangeably. Methods: Ten commercially available second-generation anti-tTG assays were evaluated. The following populations were studied: celiac disease (CD) patients at the time of diagnosis without (n ‫؍‬ 70) or with (n ‫؍‬ 5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 43 publications
6
86
1
2
Order By: Relevance
“…The excellent diagnostic performance of tests for antitTG and EMA antibodies has enabled the hidden part of the celiac iceberg to be identified in recent years (20,21). The current prevalence of CD in the Western countries is estimated at between 1:80 and 1:100 (16,(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The excellent diagnostic performance of tests for antitTG and EMA antibodies has enabled the hidden part of the celiac iceberg to be identified in recent years (20,21). The current prevalence of CD in the Western countries is estimated at between 1:80 and 1:100 (16,(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…The current prevalence of CD in the Western countries is estimated at between 1:80 and 1:100 (16,(20)(21)(22)(23)(24). Identification of anti-tTG and EMA antibodies as a marker for CD has caused AGA to lose the diagnostic role they had held since the early 80s (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, discordant data between adults and children have been reported as the anti-tTG assay is less accurate in very young patients and autoantibody levels can fluctuate (9)(10)(11). In fact, the reported sensitivity for IgA anti-tTG, including all ages, ranges between 67% and 100%, with a specificity between 96% and 100% (5,(11)(12)(13)(14)(15)(16)(17)(18)(19), while in very young patients the sensitivity is lower, with a value ranging from 67% to 83% (11,17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Van Meensel [79] and colleagues evaluated 10 different commercially available second-generation IgA anti-tTG ELISA kits, and showed that most of these assays presented excellent performance, with good linear ranges. According to the optimal receiver operating characteristics (ROC) curve cutoff employed, the sensitivity values ranged from 91 to 97% and the specificity ranged between 96 and 100%.…”
Section: Biological Markersmentioning
confidence: 99%